The Born in Bradford COVID-19 Research Study: Protocol for an adaptive mixed methods research study to gather actionable intelligence on the impact of COVID-19 on health inequalities amongst families living in Bradford - McEachan, Rosemary R C (Wellcome Open Res, 2020)
The UK COVID-19 lockdown has included restricting social movement and interaction to slow the spread of disease and reduce demand on NHS acute services. It is likely that the impacts of restrictions will hit the least advantaged disproportionately and will worsen existing structural inequalities amongst deprived and ethnic minority groups. The aim of this study is to deliver rapid intelligence to enable an effective COVID-19 response, including co-production of interventions, that address key issues in the City of Bradford, UK, and nationally. In the longer term we aim to understand the impacts of the response on health trajectories and inequalities in these. In this paper we describe our approach and protocol. We plan an adaptive longitudinal mixed methods approach embedded with Born in Bradford (BiB) birth cohorts which have rich existing data (including questionnaire, routine health and biobank). All work packages (WP) interact and are ongoing. WP1 uses co-production and engagement methods with communities, decision-makers and researchers to continuously set (changing) research priorities and will, longer-term, co-produce interventions to aid the City’s recovery. In WP2 repeated quantitative surveys will be administered during lockdown (April-June 2020), with three repeat surveys until 12 months post-lockdown with an ethnically diverse pool of BiB participants (parents, children aged 9-13 years, pregnant women: total sample pool N=7,652, N=5,154, N=1,800). A range of health, social, economic and education outcomes will be assessed. In WP3 priority topics identified in WP1 and WP2 will be explored qualitatively. Initial priority topics include children’s mental wellbeing, health beliefs and the peri/post-natal period. Feedback loops will ensure findings are fed directly to decision-makers and communities (via WP1) to enable co-production of acceptable interventions and identify future priority topic areas. Findings will be used to aid development of local and national policy to support recovery from the pandemic and minimise health inequalities.